Neutrophils from Alzheimer’s disease mice fail to phagocytose debris and show altered release of immune modulators with age - Kays, Matthew; Kelly, Anna; McGinnis, Farrah; Woods, Clara; Herron, Emily; Brown, Candice; Coulibaly, Aminata P. (Frontiers in Immunology, 2025)
Recent reports show that neutrophil activity plays a role in the cognitive decline associated with Alzheimer’s Disease (AD). There is evidence of altered functions in neutrophils isolated from AD patients. Whether these altered functions are inherent to the AD disease state is unknown. The goal of this study was to determine if neutrophil functions are altered in AD mice and if these changes occur only after symptoms appear. To address this hypothesis, we used a primary neuronal culture model, generated from 3xTg perinatal mice, since AD is considered a CNS disease. The 3xTg primary neuronal culture gradually increase the release of Aβ (40 and 42) as the culture ages. To assess neutrophil functions, neutrophils isolated from young male/female mice (3–6 months of age) or aged male/female mice (16–18 months of age) of WT or 3xTg mice were exposed to 3xTg primary neuronal cultures. To assess phagocytosis, we characterized the effect of neutrophils on pathogenic amyloid beta (Aβ) 42 levels. To assess the levels of immune modulators (cytokines, chemokines, growth factors, NETosis, and neutrophil granular content), culture media were assessed using Luminex multiplex assay. Our results show that neutrophils from young AD mice have impaired phagocytosis, as observed in a decreased ability to remove Aβ and cellular debris in vitro. Neutrophils from young AD mice also increased release of pro-inflammatory cytokines, granule content, and NETs in 3xTg primary neuronal cultures. Interestingly, neutrophils from aged 3xTg mice decreased Aβ levels in culture and expression of proinflammatory cytokines when compared to neutrophils from aged WT mice. These neutrophils increased their release of granule content and NETs in 3xTg primary neuronal cultures. These data show that in AD neutrophil function is altered in (young mice) and diseased (old mice) stage.